Reclaiming stewardship in Ghana religion and climate change - Golo, B.-W.K.; Yaro, J.A. (Nature and Culture, 2013)
The hydra-headed nature of climate change-affecting not just climate but all other domains of human life-requires not just technological fixes but cultural innovation. It is impossible to ignore a devoutly religious majority in Ghana, a nation where diverse religious communities' perspectives on climate change and their views on the way forward are crucial. This article aims to empirically explore how Christian, Islamic, and indigenous African religious leaders view the challenges of climate change and what countermeasures they propose. Interestingly, most our informants have indicated that the reasons for the current environmental crisis are, in equal degree, Ghana's past colonial experience and deviation from religious beliefs and practice, while the main obstacle to sustainable development is poverty. There was unanimity on the reclamation of religious values and principles that promote the idea of stewardship as a way forward toward a sustainable future. This, however, functions more as a faith claim and a religiously inspired normative postulate than a program of concrete action.
Keywords: Climate change; Developmental preservation; Religious perspectives; Stewardship; Sustainability